The impact of teacher professional conduct on learner experiences and performance in poor school communities in South Africa. Issue 4 (4th July 2019) - Munje, Paul Nwati
Abstract: A qualitative based study was undertaken to explore the impact of teacher professional conduct on learner experiences and performance in three poor primary schools in a disadvantaged community in Cape Town, South Africa. Data was gathered through individual and focus-group interviews, observations and document reviews. The paper uses the capabilities approach to show how teacher professional conduct impact on the aspirations of primary school learners. The paper highlights the silent role limited learning resources, contextual challenges, learner backgrounds, dysfunctional school management systems and policy play in exacerbating teacher unprofessionalism and learner unfreedoms in high-poverty-level areas. It also stresses the critical role the education system has to play in normalising teacher professional conduct by reassessing the impact of these constraints in the classroom. Teachers as part of the change process have to be accountable for their own actions and also voluntarily change their attitudes when dealing with learners.